Normative course «Method of teaching of pedagogical disciplines in higher educational establishments» in forming of methodical culture of future teachers (Pedagogy of Higher and Secondary Education, 2013)
Knyazheva I. A. Normative course «Method of teaching of pedagogical disciplines in higher educational establishments» in forming of methodical culture of future teachers.In the article there is considered the maintenance of the author program of course «Method of teaching of pedagogical disciplines in higher educational establishments», used by the mean of forming of methodical culture of future teachers. An author specifies maintenance of concept «Methodical culture of future teachers».
Keywords: methodical culture; future teachers; teaching method; pedagogical disciplines; higher educational establishment